AB1130 Relapse risk assessment in young aps patients with previous stroke event using the adjusted global antiphospholipid syndrome score (AGAPSS). (15th June 2017) - Cecchi, I; Radin, M; Schreiber, K; Cuadrado, MJ; Perez-Sanchez, C; Lopez-Pedrera, C; Roccatello, D; Sciascia, S
Abstract : Background: The most frequent manifestation of arterial thrombosis in patients affected by Antiphospholipid syndrome (APS) is ischaemic stroke, especially in young adults (less than 50 years old) [1]. Young adults affected by APS are a group of patients at greater risk of developing serious stroke events and recurrences of thrombosis. Therefore, risk stratification in this particular group is crucial, especially in order to prevent a recurrence of ischaemic thrombotic event. Objectives: With the present study we aimed to assess the clinical usefulness of the adjusted Global AntiphosPholipid Syndrome Score (aGAPSS) [3] for risk stratification of thrombosis relapse and/or progression of known ischaemic lesions dectected with Magnetic Resonance Imaging (MRI) in a cohort of young adult APS patients. Methods: The analysis included 80 APS patients (≤50 years old) who presented a previous stroke event (patients who experienced cerebral venous sinus thrombosis were not included in the analysis). Clinical and laboratory data were retrospectively collected. Treatment was based on phisician's opinion according to clinical settings. The aGAPSS was calculated for each patient by adding the points corresponding to the risk factors, based on a linear transformation derived from the β regression coefficient as follows: 3 for hyperlipidaemia, 1 for arterial hypertension, 5 for aCL IgG/IgM, 4 for antiβ2glycoprotein I IgG/IgM and 4 for LA. Relapse was defined as the recurrence of thrombotic event and/or progression of known ischaemic lesions detected with MRI. Results: Results pointed out that patients with relapse of thrombotic events and/or progression of known ischaemic lesions were 39 out of 80 (48.7%) and patients without relapse were 41 out of 80 (51.3%). Significantly higher aGAPSS values were observed in relapse group when compared to the non-relapse group [mean aGAPSS 9.08 (S.D. 4.7) Vs. mean aGAPSS 7.22 (S.D. 3.3); T test: p<0.05]. Distribution of aGAPPS values among the two groups is illustrated in Graph 1. Conclusions: Our analysis suggests that aGAPSS could represent an effective tool to stratify the risk of relapse of thrombosis and/or progression of ischaemic lesions in young APS patients with clinical history of stroke. These data could also aid developing different therapeutic approaches, especially for patients at higher risk of relapse. References: Tektonidou MG, Varsou N, Kotoulas G, Antoniou A, Moutsopoulos HM. Cognitive deficits in patients with antiphospholipid syndrome: association with clinical, laboratory, and brain magnetic resonance imaging findings. Arch Intern Med 2006;166(20):2278–84. Meroni PL, Borghi MO, Raschi E, Tedesco F. Pathogenesis of antiphospholipid syndrome: understanding the antibodies. Nat Rev Rheumatol. 2011;7:330–9. Sciascia S, Sanna G, Murru V, Roccatello D, Khamashta MA, Bertolaccini ML. GAPSS: The Global Anti-Phospholipid Syndrome Score. Rheumatology (Oxford) 2013; 52:1397–403. Acknowledgements: None. Disclosure of Interest: None declared